Variable geometry mixed flow turbine for turbochargers: an experimental study - Rajoo, Srithar; Botas, Ricardo Martinez (Japan Science and Technology Information Aggregator, Electronic, 2008)
This paper investigates a variable geometry (VG) mixed flow turbine with a novel, purposely designed pivoting nozzle vane ring. The nozzle vane ring was matched to the 3-dimensional aspect of the mixed flow rotor leading edge with lean stacking. It was found that for a nozzle vane ring in a volute, the vane surface pressure is highly affected by the flow in the volute rather than the adjacent vane surface interactions, especially at closer nozzle positions. The performance of the VG mixed flow turbine has been evaluated experimentally in steady and unsteady flow conditions. The VG mixed flow turbine shows higher peak efficiency and swallowing capacity at various vane angle settings compared to an equivalent nozzleless turbine. Comparison with an equivalent straight vane arrangement shows a higher swallowing capacity but similar efficiencies. The VG turbine unsteady performance was found to deviate substantially from the quasi-steady assumption compared to a nozzleless turbine. This is more evident in the higher vane angle settings (smaller nozzle passage), where there are high possibility of choking during a pulse cycle. The presented steady and unsteady results are expected to be beneficial in the design of variable geometry turbochargers, especially the ones with a mixed flow turbine